PENEGAKAN HUKUM WARGA NEGARA ASING YANG MENGENDARAI SEPEDA MOTOR SEWA OLEH SATUAN LALU LINTAS POLRESTA DENPASAR - Pradnya Putra, I Gusti Ngurah Eka Pradnya Putra (Fakultas Hukum Universitas Dwijendra, 2026)
In Bali, foreign tourists who drive motorized vehicles, both two-wheeled and four-wheeled vehicles to go to tourist attractions. According to Article 281 junto Article 77 paragraph (1) Number 22 of 2009 concerning Traffic and Road Transportation, that everyone who drives a motorized vehicle on the road is obliged to obey traffic regulations. The increase in violations by foreign tourists is the task of the Polresta Traffic Unit to take firm action against violators. The purpose of the study was to determine law enforcement against Foreign Citizens who ride rented motorbikes by the Denpasar Police Traffic Unit and the obstacles and efforts to enforce the law against Foreign Citizens who ride rented motorbikes by the Denpasar Police Traffic Unit. This type of research is empirical legal research, namely research with field data as the main data source, such as interview results and observations. There are two types of data used, namely primary data obtained from Members of the Denpasar Police Traffic Unit through interviews and direct research. Secondary data obtained through literature studies of various studies. The conclusion of the study on law enforcement of Foreign Citizens riding rented motorbikes by the Denpasar Police Traffic Unit is that Foreign Citizens (WNA) riding rented motorbikes by the Denpasar Police Traffic Unit use Law Number 22 of 2009 concerning Traffic and Road Transportation as a guideline in taking action against violations. Obstacles in law enforcement are factors of legislative constraints, law enforcement, facilities and infrastructure and the community. Efforts that can be made by the Traffic Unit are to apply preemptive (education), preventive (prevention), and repressive (law enforcement or sanctions) methods.